2018
DOI: 10.1111/infa.12261
|View full text |Cite
|
Sign up to set email alerts
|

Gaze following in 4.5‐ and 6‐month‐old infants: The impact of proximity on standard gaze following performance tests

Abstract: Gaze following (GF), the ability to synchronize visual attention with others, is often considered a foundation of social cognition. In this study, GF was assessed while changing the space between an actor's eyes and the gaze target. This was done to address a potential confound in the gold standard GF performance test, namely the spatial bias of the actors’ eye position that occurs when the actor turns the head to look at a target, offsetting the eye position from a centered position toward the attended target… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
11
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 42 publications
5
11
2
Order By: Relevance
“…Using optical flow, learning the correct gaze direction was superior for tapping, followed by pointing with movement and, last, pointing without movement. These results underpin the hypothesis that deictic comprehension in infants is facilitated by moving gestures [1,18].…”
Section: Related Worksupporting
confidence: 56%
“…Using optical flow, learning the correct gaze direction was superior for tapping, followed by pointing with movement and, last, pointing without movement. These results underpin the hypothesis that deictic comprehension in infants is facilitated by moving gestures [1,18].…”
Section: Related Worksupporting
confidence: 56%
“…The second interpretation would take on the experiential account and argue that preference for the human gaze is due to the inexperience that infants have with the gaze of other species or entities, like robots. Several studies have shown that gaze following develops within 12 months 33 , 40 45 , although the debate is still open on the exact onset period 5 , 7 , 9 , 24 , 31 , 46 , 47 . At this age, infants appear to be selectively attuned to follow the human gaze, and this would be in line with findings showing that 12-month old infants have difficulties in following the gaze of other species 39 .…”
Section: Discussionmentioning
confidence: 99%
“…One interpretation is that this pattern may reflect the early emergence of gaze following (i.e., the ability to look where another individual is looking). Gaze following begins to develop as early as 2 to 4 months of age (Astor & Gredebäck, ; D'Entremont, ; Gredebäck, Fikke, & Melinder, ; Perra & Gattis, ), and stabilizes by around 6 to 12 months (De Groote, Roeyers, & Striano, ; Morales, Mundy, & Rojas, ; Triesch, Teuscher, Deák, & Carlson, ). At first this effect may seem counter‐intuitive.…”
Section: Discussionmentioning
confidence: 99%